Pengaruh Model Outdoor Learning terhadap Pemahaman Sejarah Mahasiswa Pendidikan Sejarah - Nilan Loliyana; Geraldius Maria Sukamto; Endang Sri Andayani (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The purpose of this study was to determine the effect of the outdoor learning models on the historical understanding of 2018 generation students of State University of Malang. This study connects nature and historical material as a source of student learning. The results showed the acquisition of experimental class post-test values using the outdoor learning model was higher when compared to the control class using conventional models. The average value of students in the control class is 42.35 while in the experimental class is 68.62. Based on these results, it can be concluded that the model of outdoor learning is classified as feasible and well used in the process to improve historical understanding.Abstrak: Tujuan penelitian ini untuk mengetahui pengaruh model pembelajaran outdoor learning terhadap pemahaman sejarah mahasiswa sejarah angkatan tahun 2018 Universitas Negeri Malang. Penelitian ini menghubungkan alam dan materi sejarah sebagai sumber belajar mahasiswa. Hasil penelitian menunjukkan perolehan nilai posttes kelas eksperimen dengan menggunakan model outdoor learning lebih tinggi jika dibandingkan kelas kontrol dengan menggunakan model konvensional. Nilai rata-rata mahasiswa pada kelas kontrol 42.35, sedangkan pada kelas eksperimen 68.62. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model pembelajaran outdoor learning tergolong layak dan dan baik digunakan dalam proses untuk meningkatkan pemahaman sejarah.